Draft Annual Plan 1970-71 Government of Assam - Planning Commission (Planning Commission, 1970)
Assam, a land-locked State standing like a sentinel guard on the north-eastern frontier of the country, is flanked on three sides by the foreign territories of China, Burma and East Pakistan, It is the core of the entire strategic North-eastern region of the country comprising Assam, N.F.F.A,, Nagaland, Manipur and Tripura.
Government of Assam, Planning and Development Department